2015
DOI: 10.1371/journal.pone.0122160
|View full text |Cite
|
Sign up to set email alerts
|

The ϕ6 Cystovirus Protein P7 Becomes Accessible to Antibodies in the Transcribing Nucleocapsid: A Probe for Viral Structural Elements

Abstract: Protein P7 is a component of the cystovirus viral polymerase complex. In the unpackaged procapsid, the protein is situated in close proximity to the viral directed RNA polymerase, P2. Cryo-electron microscopy difference maps from the species ϕ6 procapsid have demonstrated that P7 and P2 likely interact prior to viral RNA packaging. The location of P7 in the post-packaged nucleocapsid (NC) remains unknown. P7 may translocate closer to the five-fold axis of a filled procapsid but this has not been directly visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…6A). This morphology is consistent with that in micrographs of the icosahedral nucleocapsid (Alimova et al, 2015), indicating that the viral envelope has been disassembled during aggregation with goethite.…”
Section: Tem Analysissupporting
confidence: 84%
“…6A). This morphology is consistent with that in micrographs of the icosahedral nucleocapsid (Alimova et al, 2015), indicating that the viral envelope has been disassembled during aggregation with goethite.…”
Section: Tem Analysissupporting
confidence: 84%
“…Indeed, it remains unclear if the protein exists as a dimer or monomer when assembled within the capsid. The data from our own research efforts [ 28 , 32 , 81 ] strongly suggested a structural role for a monomeric protein as a stabilization element for the P2 polymerase prior to and during transcript packaging. The absence of P7 PC particles showed a random distribution of P2 monomers throughout the particle in support of this notion.…”
Section: Conclusion and Suggestions For Additional Areas Of Investiga...mentioning
confidence: 99%
“…Our group proposed that P7 is located “inside” the PC core near the inner three-fold axes, and P7 stabilizes P2 in a position close to the three-fold axis [ 32 ]. We noted that using antibody reagents, during phi6 NC transcription, the P7 becomes accessible to the antibody, implying the loosen P1 matrix and P8 shell during the transcription [ 81 ]. The P7 protein has very low similarity between species by sequence, but structurally they are very similar.…”
Section: The Precise Function and Positioning Of Protein P7mentioning
confidence: 99%